Endgame for the West in Afghanistan? explaining the decline in support for the war in Afghanistan in the United States, Great Britain, Canada, Australia, France and Germany - Miller, Charles A. (Strategic Studies Institute, U.S. Army War College, 2010)
Analyses of the War in Afghanistan frequently mention the declining or shaky domestic support for the conflict in the United States and among several U.S. allies. This paper dates the beginning of this decline back to the resurgence of the Taliban in 2005-06 and suggests that the deteriorating course of the war on the ground in Afghanistan itself along with mounting casualties is the key reason behind this drop in domestic support for the war
"June 2010."
Includes bibliographical references (p. 130-166)
Introduction -- The good war? : American public opinion and the war in Afghanistan -- Casualties -- Casualties plus politics -- Afghan-specific explanations -- The "deputy sheriff" : Australian public opinion and the Afghan war -- Casualties -- Casualties plus politics -- Afghanistan-specific theories -- Back on Afghanistan's plains : public support for the Afghan war in Britain -- Casualties -- Casualties plus politics -- Afghan-specific theories -- Farewell to the blue helmets : Canadian public opinion on Afghanistan -- Casualties -- Casualties plus politics -- Afghanistan-specific theories -- Conclusion -- Sarkozy's war : France takes to the frontline -- Casualties -- Casualties plus politics -- Afghanistan-specific theories -- Still struggling with the guilt of the past : Germany's Afghan agonies -- Casualties -- Casualties plus politics -- Afghanistan-specific theories -- Conclusion -- Summary
Keywords: Taliban / Influence; NATO; Geschichte 2002-2009; Afghan War, 2001- / Casualties; Afghan War, 2001- / United States / Public opinion; Afghan War, 2001- / Foreign public opinion, British; Afghan War, 2001- / Foreign public opinion, Canadian; Afghan War, 2001- / Foreign public opinion, Australian; Afghan War, 2001- / Foreign public opinion, French; Afghan War, 2001- / Foreign public opinion, German; Öffentliche Meinung; Afghanistankrieg -- 2001-2021; USA